Respuesta :

1.  L.C.M of the denominators is 4.

So, multiply the numerator and the denominator of the first fraction by 2.

[tex]\frac{1}{2} + \frac{3}{4} =\frac{2}{4} +\frac{3}{4}[/tex]

[tex]=\frac{5}{4}[/tex]

Hence, [tex]\frac{1}{2} +\frac{3}{4} =\frac{5}{4}[/tex].

2.  L.C.M of the denominators is 24.

So, multiply the numerator and the denominator of the first fraction by 4 and those of the second fraction by 3.

[tex]\frac{1}{6} +\frac{3}{8} =\frac{4}{24} +\frac{9}{24}[/tex]

[tex]=\frac{13}{24}[/tex]

Hence, [tex]\frac{1}{6} +\frac{3}{8} =\frac{13}{24}[/tex].

3.  L.C.M of the denominators is 24.

So, multiply the numerator and the denominator of the first fraction by 3 and those of the second fraction by 2.

[tex]\frac{7}{8}- \frac{5}{12} =\frac{21}{24} -\frac{10}{24}[/tex]

[tex]=\frac{11}{24}[/tex]

Hence, [tex]\frac{7}{8} -\frac{5}{12} =\frac{11}{24}[/tex].

ACCESS MORE